Misturas de cereais de inverso de duplo propósito para silagem de planta inteira - Dall'Agnol, Emanuel Cassol (2022)
Forage conservation as silage is an essential technique for animal production due to the seasonality of forage production throughout the year, with times of surplus and others of shortages in forage production. In addition, the use of small grains as ruminants feed is characterized as an economic and environmentally viable alternative because it uses unoccupied areas during the winter. The mixture of cultivars or even species of small grains for silage meets the necessity to extend the harvest period, reduce risks with losses due to weather conditions and improve the cost/benefit ratio for the farmer. Mixtures of whole plant small grains were made during the 2020 year, with the objectives of evaluating the feasibility of use, the chemical characteristics of the resulting silages, and leaf/stem/cob or panicle partition of the cultivars. The first part of the research was carried out in the experimental field of Embrapa Trigo in Passo Fundo - RS, in randomized blocks, with four wheat cultivars (BRS Pastoreio, BRS Tarumaxi, BRS Tarumã and TBio Energix 201), amd a black oat cultivar (Embrapa 139 – Neblina). The second part was carried out in a place sheltered from rain, sun and extreme temperature variations, in a completely randomized design. The treatments were PVC silos containing the silages of the aforementioned cultivars and the mixtures Tbio Energix/Embrapa Neblina, BRS Tarumã/BRS Pastoreio, BRS Tarumaxi/BRS Pastoreio, Tbio Energix/BRS Pastoreio, and the mixture of two barley cultivars (BRS Quaranta/BRS Korbel). All silages showed adequate fermentative profile and satisfactory nutritional characteristics to meet the demand of dairy farms or confined cattle. The wheat cultivar BRS Pastoreio can be mixed with Tbio Energix, BRS Tarumã and BRS Tarumaxi, anticipating or extending the harvest period by 15 days. The wheat cultivar BRS Pastoreio had a higher proportion of cob compared to the others.